NORMATIVE AND TECHNICAL REGULATION OF WORKS TO INCREASE THE VEHICLES RESOURCE - Dvoretskyi, V. I. (Science and Transport Progress, 2006)
In the article there are the considered questions of the normatively-technical adjusting of works for the increases of resource of transporting machines.